PEMODELAN LAJU RESPIRASI BUAH KLIMAKTERIK SELAMA PENYIMPANAN PADA SUHU YANG BERVARIASI - Dwi Rahayu; Nursigit Bintoro; Arifin Dwi Saputro (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Most of Indonesia’s fresh produces are belong to the climacteric group, which needs certain handling, especially for storage management. Information on the respiration rate in various temperatures and times is an important aspect on designing the storage room. This research aimed to measure the respiration rate of banana, guava, and mango. Respiration rate was measured with a closed system respirometer at temperatures 10, 15, and 28oC. The data used to develop mathematical modeling based on Michaelis-Menten (MM) and Arrhenius equations for predicting the respiration rate. Each treatment has a different agreement with each type of Michaelis-Menten’s models, however, most of the treatment has a good agreement with MM type combination. Furthermore, all showed a good fit with Arrhenius’s model and regression determination values are closed with unity. The statistical analysis used was SPSS ver. 20 software with a 3-way repeated measure method to identify the interaction between treatment and respiration rate (RO2 and RCO2). Significant interaction among treatment was found for RCO2. The best temperature to store fruit was found at 15oC.